New nanolimes for eco-friendly and customized treatments to preserve the biocalcarenites of the "Valley of Temples" of Agrigento. (1st November 2021) - Macera, L.; Daniele, V.; Duchetta, F.; Casciardi, S.; Taglieri, G.
Highlights: Eco-friendly and customized conservative treatments on Agrigento biocalcarenites. New aqueous nanolime formulations, pure or properly chemically tailored. Nanolime is produced by a single-step, time/energy-saving and scalable route. The carbonation process of the nanolime formulations was investigated. Treatment effectiveness and durability is evaluated by means of standard procedures. Abstract: In this paper we introduce new aqueous nanolime formulations, pure or properly chemically tailored, for innovative, compatible, and eco-friendly consolidation treatments on biocalcarenite stones, a renowned kind of stones used in ancient buildings throughout the Mediterranean region, which are however subject to severe decay. The phase composition, stability, and carbonation process of the nanolime formulations were investigated, while the treatments efficacy was evaluated in terms of aesthetical features, superficial cohesion, drilling resistance and durability. The aqueous nanolimes, applied by nebulization, increased the mechanical resistance on the surface and up to 2 cm in depth without appreciable surface variations, especially in the case of the tailored formulation, ensuring a good durability to UV/salt crystallization ageing.